Block-holders and monitoring mechanisms in Nigeria - Oluyemisi Rachael Arowolo,; Ayoib Che Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Companies continue to fold up after the global economic melt-down of 2008 starting with the Enron saga. One of the reasons offered by practitioners and intellectuals in their search for the cause and solution to the problem is information asymmetry between the managements and the shareholders. It is extremely necessary ever since the sagas and continuous business failures and financial distress in Nigeria, in particular, to focus on monitoring mechanisms (MM), especially in Sub-Saharan countries. In addition, it is essential to understand the factors relating to MM as it cannot work in isolation. The purpose of this study is therefore to examine the extent to which block-holders impact on MM using the annual reports of 111 Nigerian non-financial listed companies in the context of agency theory. In addition, data were collected from the companies in respect of their internal auditing using the questionnaire as these are not available in the annual reports. The findings provide evidence that the block-holders significantly relate to monitoring mechanisms. Thus, this paper provides a new knowledge regarding monitoring mechanisms and its antecedents (directorship, internal and external auditing). These findings are with policy implications for the board of directors to implement their monitoring responsibilities. The findings also suggest policy implications for the internal and external auditors. The findings are useful for further review of corporate governance guidelines by the regulatory agencies and government. The paper contributes to knowledge in Sub-Saharan Africa, Nigeria in particular by examining block-holders in relation to the aggregate cost of monitoring mechanisms (directorship, internal and external auditing).